Supporting climate-resilient food systems policies and institutions in Latin America - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
This extensive project has struck up collaborations across Latin America to assist policy makers incorporate the latest climate and agriculture science and tools in national adaptation and mitigation plans.